Cultivar discrimination/segregation of representative Australian malting barley by quantitative real‐time PCR using seed hordein marker. Issue 4 (28th October 2016) - Cai, Guolin; You, Lihua; Li, Xiaomin; Wu, Dianhui; Lu, Jian
Abstract : The malting barley cultivar greatly affects the quality traits of malt, and thus that of final beer product. A fast, sensitive and quantitative method of barley variety discrimination is needed for maltsters. In the present study, six commonly used varieties in Chinese brewing industry, including the Australia malting barley varieties (Gairdner, Baudin, Hindmarsh and Vlamingh) and Chinese ones (Supi6 and Kenpi7) were selected for new method development. A two‐dimensional electrophoresis profile of seed hordeins was obtained to explore the representative markers of each variety. By comparing the hordein profiles, 43 common spots and 14 specific spots that presented in only one barley cultivar gel were investigated and identified by matrix‐assisted laser desorption/ionization time‐of‐flight. The blended Gairdner barley samples with a series of purity degrees were obtained by artificial mixing Gairdner seeds with those of Supi6 and Kenpi7 in the laboratory. Standard curves regarding the transcriptional level of hordein marker BMAI‐1 to the variety purity of Gairdner were set using quantitative real‐time PCR (qRT‐PCR). Finally, the developed method based on qRT‐PCR was shown to be accurate and time‐saving compared with the conventional SDS–PAGE method by a double blind experiment. Copyright © 2016 The Institute of Brewing & Distilling